Методичні вказівки до виконання індивідуального завдання з дисципліни "Управління стратегічними змінами" - Прохоренко, Олена Вікторівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
The course “Strategic change management” is aimed at students mastering the principles and methods of managing strategic changes in the organization, namely the factors that determine the need for changes, strategies and tactics for implementing changes, overcoming resistance to changes. The goal of the course is to reveal the theoretical and methodological foundations and practical tools of strategic change management as the basis of effective strategic management. The main emphasis in the formation of the content of the course is made on highlighting the aspects of change management closest to practice in view of the general systemic understanding of the process of strategic management of the enterprise. The course tasks are following: - research of modern theories of change management and possibilities of their practical application; - mastering the methods of evaluating external drivers of change and the strategic potential of change; - familiarization with the mechanisms of assessment, mitigation and elimination of resistance to strategic changes at enterprises; - outlining the role of corporate culture and mastering the tools of its development in conditions of strategic changes; - mastering modern methods of strategic change management.
A manual for individual task on course "Strategic change management"
Keywords: a manual; general characteristics of the organization; stage of life cycle; identifying the object of change; stakeholders; participants in strategic change; key steps in the implementation plan